THE PECULARITIES OF CREATION AND IMPLEMENTATION OF NATIONAL INDUSTRIAL POLICIES IN FOREIGN COUNTRIES IN THE TIMES OF INNOVATIONAL ECONOMICS - N. Volkova; A. Naboychenko (Вестник университета, 2016)
Thе article reviews various peculiarities of formation and implementation of industrial policy in foreign countries that maintain different types of industrial policy. Moreover, it contains the analysis of the foreign experience. It also highlights the prospects for the implementation of foreign experience in Russian Federation, as well as its pros and cons.